PENGARUH STRES KERJA DAN KONFLIK TERHADAP KINERJA KARYAWAN (STUDI KASUS PT POS INDONESIA KANTOR CABANG PEKANBARU) - Rosliana Silali; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of job stress and conflict to performance of employees at PT Pos Indonesia KC Pekanbaru partially and simultaneously. This type of research used in this research is the explanation (explanatory research) with a quantitive approach to describe the relationship between variable through hypothesis testing. This study used a quostionnare as a data collection tool that is distributed to 30 respondents from PT Pos Indonesia KC Pekanbaru.Based on the result of research conducted, the partial job stress has a significant effect on employee performance PT Pos Indonesia KC Pekanbaru, partial variable conflict is not significantly influence employee performance PT Pos Indonesia KC Pekanbaru, as shown by the significant value greater than 0, 05. And simultaneous assessment of job stress and conflict have a significant effect on employee performance. Based on research obtained the degree of correlation of 0.495 which indicates that the level of relationship between the independent variable on the dependent variable has a strong relationship and R² values obtained at 0.245 or 24.5%. This means that employee performance PT Pos Indonesia KC Pekanbaru influenced by the job stress and conflict amounted to 24.5%.Keywords: Job Stress, Conflict, Employee Performance